ANALISIS TEORI PENDEKATAN SITUASIONAL UNTUK GURU WALI KELAS BAGI TRANSFORMASI KEBERHASILAN PEMBELAJARAN SISWA [ANALYSIS OF THE SITUATIONAL APPROACH THEORY FOR HOMEROOM TEACHERS FOR TRANSFORMING ACHIEVEMENT OF STUDENT LEARNING] - Tikno Iensufiie (Universitas Pelita Harapan, 2020)
Homeroom teachers have many other tasks besides teaching such as guiding their students in an organized manner as a group towards the same goal of a successful learning process. The homeroom teacher has a mandate from God to have a positive influence as